Multiple‐dose ponezumab for mild‐to‐moderate Alzheimer's disease: Safety and efficacy. Issue 3 (10th May 2017) - Landen, Jaren W.; Cohen, Sharon; Billing, Clare B.; Cronenberger, Carol; Styren, Scot; Burstein, Aaron H.; Sattler, Catherine; Lee, Jae‐Hong; Jack, Clifford R.; Kantarci, Kejal; Schwartz, Pamela F.; Duggan, William T.; et al.
Abstract: Introduction: Multiple intravenous doses of ponezumab, an anti‐amyloid antibody, were evaluated in subjects with mild‐to‐moderate Alzheimer's disease (AD). Methods: In part A, 77 subjects were randomized to ponezumab 0.1, 0.5, or 1 mg/kg (75 treated) and 26 to placebo (24 treated). In part B, 63 subjects were randomized and treated with ponezumab 3 or 8.5 mg/kg and 32 with placebo. Subjects received 10 infusions over 18 months and were followed for 6 months thereafter. Results: Ponezumab was generally safe and well tolerated. Most common adverse events were fall (16.7% ponezumab, 21.4% placebo), headache (13.8%, 21.4%), and cerebral microhemorrhage (13.8%, 19.6%). Plasma ponezumab increased dose‐dependently with limited accumulation. Cerebrospinal fluid penetration was low. Plasma Aβ1–x and Aβ1–40 showed robust increases, but cerebrospinal fluid biomarkers showed no dose response. Ponezumab had no effects on cognitive/functional outcomes or brain volume. Conclusions: Multiple‐dose ponezumab was generally safe, but not efficacious, in mild‐to‐moderate AD.